2007
DOI: 10.1118/1.2779127
|View full text |Cite
|
Sign up to set email alerts
|

IMRT planning and delivery incorporating daily dose from mega‐voltage cone‐beam computed tomography imaging

Abstract: The technology of online mega-voltage cone-beam (CB) computed tomography (MV-CBCT) imaging is currently used in many institutions to generate a 3D anatomical dataset of a patient in treatment position. It utilizes an accelerator therapy beam, delivered with 200 degrees gantry rotation, and captured by an electronic portal imager to account for organ motion and setup variations. Although the patient dose exposure from a single volumetric MV-CBCT imaging procedure is comparable to that from standard double-expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 27 publications
(25 reference statements)
2
46
0
Order By: Relevance
“…Since the dose received from pre-treatment verification imaging can be considerable, 3,8 it has been suggested that this dose should be accounted for at the treatment planning stage. 3,29,30 Although this allows for the correct calculation of normal tissue and tumour dose, imaging dose incorporation has the potential to impact the treatment efficacy in an adverse manner. This is because in the time between pre-treatment imaging and delivery of the remaining treatment dose, sublethal damage repair may occur, 31 which may lead to a reduced amount of sublethal damage that can be subsequently compounded to lethal damage by the treatment dose.…”
Section: Discussionmentioning
confidence: 99%
“…Since the dose received from pre-treatment verification imaging can be considerable, 3,8 it has been suggested that this dose should be accounted for at the treatment planning stage. 3,29,30 Although this allows for the correct calculation of normal tissue and tumour dose, imaging dose incorporation has the potential to impact the treatment efficacy in an adverse manner. This is because in the time between pre-treatment imaging and delivery of the remaining treatment dose, sublethal damage repair may occur, 31 which may lead to a reduced amount of sublethal damage that can be subsequently compounded to lethal damage by the treatment dose.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ding et al reported the detailed information concerning the additional imaging doses to patients' radiosensitive organs from a KV CBCT scan; for an abdominal scan, the mean doses were 3 and 7 cGy to the prostate and 7 and 17 cGy to the femoral heads for a large adult patient and a 31-month-old pediatric patient, respectively [17]. Recently, a method to incorporate the daily megavoltage CBCT dose into the IMRT planning process was developed and implemented in the treatment of prostate cancer patients [18]. This technique has the potential to greatly improve the accuracy of treatment delivery, while maintaining target coverage and sparing the organs at risk.…”
Section: Discussionmentioning
confidence: 99%
“…
Sophisticated radiotherapy techniques like fractionated stereotactic radiotherapy (FSRT) or intensity-modulated radiotherapy (IMRT) allow for high dose deposition to the target volume, while sparing adjacent normal tissue by steep dose gradients [5,11,12,15,16,19,21,22,23]. Depending on the chosen immobilization device, variations in daily treatment set-up regarding patient and organ movement have been reported [1,3,8].
…”
mentioning
confidence: 99%
“…The purpose of our study was to establish a practical method to handle the additional patient dose of MV-CBCT for IGRT/IMRT. Only a few reports on patient dose considerations for routine short scan MV-CBCT imaging in the head and neck and pelvis regions can be found in the literature [11,13]. However, There are areas with lower doses and areas with higher doses.…”
mentioning
confidence: 99%